Hierarchically porous nitrogen-rich carbon derived from wheat straw as an ultra-high-rate anode for lithium ion batteries - Chen, Li; Zhang, Yongzhi; Lin, Chaohong; Yang, Wen; Meng, Yan; Guo, Yong; Li, Menglong; Xiao, Dan (Journal of materials chemistry. A, Materials for energy and sustainability, 2014)
A facile, economical and effective method to produce hierarchically porous nitrogen-rich carbon (HPNC) from wheat straw has been reported. Acid pretreatment is introduced before KOH activation, and plays the role of promoting the formation of thinner pore walls. Without any N-doping, the N content is as high as 5.13%. The HPNC when used as an anode for Li-ion batteries exhibits a superior specific capacity of 1470 mA h g −1 at 0.037 A g −1 , and possesses an ultrahigh rate capability of 344 mA h g −1 at 18.5 A g −1 . Even at an extremely high current density of 37 A g −1 , the reversible capacity is still as high as 198 mA h g −1 .